A multi‐institutional phase 2 study of neoadjuvant gemcitabine and oxaliplatin with radiation therapy in patients with pancreatic cancer. Issue 15 (29th May 2013) - Kim, Edward J.; Ben‐Josef, Edgar; Herman, Joseph M.; Bekaii‐Saab, Tanios; Dawson, Laura A.; Griffith, Kent A.; Francis, Isaac R.; Greenson, Joel K.; Simeone, Diane M.; Lawrence, Theodore S.; Laheru, Daniel; Wolfgang, Christopher L.; et al.
Abstract : BACKGROUND: The purpose of this study was to evaluate preoperative treatment with full‐dose gemcitabine, oxaliplatin, and radiation therapy (RT) in patients with localized pancreatic cancer. METHODS: Eligibility included confirmation of adenocarcinoma, resectable or borderline resectable disease, a performance status ≤2, and adequate organ function. Treatment consisted of two 28‐day cycles of gemcitabine (1 g/m 2 over 30 minutes on days 1, 8, and 15) and oxaliplatin (85 mg/m 2 on days 1 and 15) with RT during cycle 1 (30 Gray [Gy] in 2‐Gy fractions). Patients were evaluated for surgery after cycle 2. Patients who underwent resection received 2 cycles of adjuvant chemotherapy. RESULTS: Sixty‐eight evaluable patients received treatment at 4 centers. By central radiology review, 23 patients had resectable disease, 39 patients had borderline resectable disease, and 6 patients had unresectable disease. Sixty‐six patients (97%) completed cycle 1 with RT, and 61 patients (90%) completed cycle 2. Grade ≥3 adverse events during preoperative therapy included neutropenia (32%), thrombocytopenia (25%), and biliary obstruction/cholangitis (14%). Forty‐three patients underwent resection (63%), and complete (R0) resection was achieved in 36 of those 43 patients (84%). The median overall survival was 18.2 months (95% confidence interval, 13–26.9 months) for all patients, 27.1 months (95% confidence interval, 21.2–47.1 months) for those who underwent resection, and 10.9 months (95% confidence interval, 6.1–12.6 months) for those who did not undergo resection. A decrease in CA 19‐9 level after neoadjuvant therapy was associated with R0 resection ( P = .02), which resulted in a median survival of 34.6 months (95% confidence interval, 20.3–47.1 months). Fourteen patients (21%) are alive and disease free at a median follow‐up of 31.4 months (range, 24–47.6 months). CONCLUSIONS: Preoperative therapy with full‐dose gemcitabine, oxaliplatin, and RT was feasible and resulted in a high percentage of R0 resections. The current results are particularly encouraging, because the majority of patients had borderline resectable disease. Cancer 2013 ;119:2692–2700. © 2013 American Cancer Society . Abstract : Preoperative therapy with full‐dose gemcitabine, oxaliplatin, and radiotherapy is feasible in patients with pancreatic cancer and results in a high percentage of complete resections. These results are particularly encouraging because the majority of patients had borderline resectable disease.